Conceptualization of Legal Protection for Prosecutors' Personal Data In Law Enforcement Processes.: Conceptualization of Legal Protection for Prosecutors' Personal Data In Law Enforcement Processes. - Windraswara, Juniardi; Pujiyono, Pujiyono; Nabitatus Sa'adah (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
A reform of State Attorney policy is required for personal data protection in the digital era to align legal frameworks with evolving technology, protect citizens' privacy rights, and address gaps in existing regulations like Indonesia's Personal Data Protection Law (UU PDP). This reform necessitates clear data management rules, robust enforcement through independent authorities, strengthened technological adaptability, and international cooperation to safeguard data against misuse and breaches while ensuring accountability in legal assistance—key Areas for Reform, Regulatory Frameworks, Data Management, Enforcement Mechanisms, Public Awareness, and Education. The rapid growth of digital technologies, especially in sectors like e-commerce and fintech, increases the risk of data leaks and misuse of personal information. Legal frameworks must evolve to keep pace with rapidly changing digital technologies to protect data and address new threats effectively. By addressing these areas, the sector of legal aid can adapt its policies to better protect personal data in the digital age and uphold fundamental human rights in a digital society.